Gluteal taping to improve gait in spastic hemiplegic cerebral palsy children: A randomized control trial: Gluteal taping to improve gait in spastic hemiplegic - Chinnavan, Elanchezhian; Ezhilarasu Ramalingam; Swarnakumari Pichai (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Cerebral palsy (CP) is the most prevalent mobility disorder in children, resulting in long-term disabilities and various impairments. The clinical manifestations of CP vary among affected individuals. CP is associated with a wide range of disorders, and a broad spec-trum of symptoms may present. Children with CP commonly experience muscle hypertonia, challenges in postural control, difficulties in ambulation, and an increased risk of falls. Objective: The primary objective of this study was to determine the impact of KT on gait metrics and functional activities following gluteal taping. Methods: The cohort study comprised 60 patients with spastic hemiplegia, aged 4–12 years, who were randomly allocated to experimental and control groups. Informed consent was obtained from all parents. The control group underwent traditional training, whereas the experimental group received gluteal taping of the affected glu-teus. Both groups participated in 45-minute training sessions three times a week for six weeks. Results: The effect of gluteal taping was evaluated using paired t-test. The post-test mean values of all gluteal taping variables demonstrated improvement compared to those of the control group (p <0.05). Conclusions: The investigators found that gluteal taping improved both gait metrics and functional abilities in participants with spastic hemiplegic cerebral palsy.